A regionalised strategy for improving motor vehicle-related highway driver deaths using a weighted averages method. Issue 1 (16th June 2011) - Kim, Tad; Rivara, Frederick P; Mozingo, David W; Lottenberg, Lawrence; Harris, Zachary B; Casella, George; Liu, Huazhi; Moldawer, Lyle L; Efron, Philip A; Ang, Darwin N
Abstract : Objective: The state of Florida has some of the most dangerous highways in the USA. In 2006, Florida averaged 1.65 fatalities per 100 million vehicle miles travelled (VMT) compared with the national average of 1.42. A study was undertaken to find a method of identifying counties that contributed to the most driver fatalities after a motor vehicle collision (MVC). By regionalising interventions unique to this subset of counties, the use of resources would have the greatest potential of improving statewide driver death. Methods: The Florida Highway Safety Motor Vehicle database 2000–2006 was used to calculate driver VMT-weighted deaths by county. A total of 3 468 326 motor vehicle crashes were evaluated. Counties that had driver death rates higher than the state average were sorted by a weighted averages method. Multivariate regression was used to calculate the likelihood of death for various risk factors. Results: VMT-weighted death rates identified 12 out of 67 counties that contributed up to 50% of overall driver fatalities. These counties were primarily clustered in central and south Florida. The strongest independent risk factors for driver death attributable to MVC in these high-risk counties were alcohol/drug use, rural roads, speed limit ≥45 mph, adverse weather conditions, divided highways, vehicle type, vehicle defects and roadway location. Conclusions: Using the weighted averages method, a small subset of counties contributing to the majority of statewide driver fatalities was identified. Regionalised interventions on specific risk factors in these counties may have the greatest impact on reducing driver-related MVC fatalities.